Drought Response in Selected Tropical Inbred Maize Lines and Relative Expression of PARP2 Gene under Limited Water Conditions - Muli, Joshua K.; Budambula, Nancy; Mweu, Cecilia; Anami, Sylvester E. (Science Publishing Group, 2018)
Drought is the leading single factor that limits maize production thus inhibiting the crops genetic potential. In response to drought, maize and other plants synthesize Poly ADP-Ribose (PAR) protein. This process is controlled by the Poly ADP-Ribose Polymerase (PARP) genes and consumes cellular energy, leading to plant death. This study evaluated four tropical inbred maize (Zea mays L.) lines; CML 216, CML 144, A04 and E04 for their response to growth limiting water stress and their relative expression of PARP2 gene under drought and non-drought conditions. The leaf lengths and growth rates of the fourth leaf were monitored for 21days post emergence while fresh and dry weights of drought stressed and non-stressed seedlings were recorded a month after emergence of the fourth leaf. The relative expression of PARP2 gene was determined using rtPCR after isolating RNA from drought stressed and non-stressed maize seedlings. There was no significant difference in the mature lengths of the fourth leaf in the four genotypes when the maize seedlings were not subjected to drought and when subjected to severe drought stress. However, subjecting maize seedlings to mild drought resulted in a significant difference in the mature leaf lengths based on the different genotypes (P= 0.0066). The growth rate of maize seedlings based on the fourth leaf was observed to be affected by drought, with a higher mean growth rate (1.74 cm day-1) registered in seedlings which were not subjected to drought and those subjected to moderate drought (1.78 cm day-1). A slower growth rate (1.37 cm day-1) was observed in seedlings subjected to severe drought stress. Fresh and dry weights of maize seedlings were also observed to be significantly different based on the level of drought exerted (P = < 0.0001) and the genotype (P = < 0.0001). The expression of PARP2 gene was found to be directly proporti
Keywords: Drought; Growth Rate; Maize; PARP